MsFtsH8 Enhances the Tolerance of PEG-Simulated Drought Stress by Boosting Antioxidant Capacity in Medicago sativa L. - Ruyue Li; Xiangcui Zeng; Xueqian Jiang; Ruicai Long; Fei He; Xue Wang; Lin Chen; Qianwen Yu; Junmei Kang; Qingchuan Yang; Tianhui Yang; Zhongkuan Liu; et al. (Plants, 2024)
Drought is a major abiotic stress that limits the growth and yield of alfalfa, a vital forage legume. The plant metalloproteinase Filamentation temperature-sensitive H (FtsH) is an ATP- and Zn2+-dependent enzyme that plays a significant character in the plant’s response to environmental stress. However, its functional role in drought resistance remains largely unexplored. This study investigates the drought tolerance role of alfalfa MsFtsH8 by analyzing the growth, physiology, and gene expression of overexpressing plants under drought conditions. The results demonstrated that both MsFtsH8-overexpressing Arabidopsis and alfalfa plants exhibited superior growth condition and enhanced membrane stability. The overexpressing alfalfa plants also showed reduced MDA levels, higher proline content, lower H2O2 accumulation, an increased activity of antioxidant-related enzymes (SOD, POD, and CAT) activity, and an elevated expression of antioxidant-related genes. These results indicated that the overexpression of MsFtsH8 enhanced growth, improved osmotic regulation, reduced ROS levels, and increased antioxidative capacity, ultimately leading to greater drought tolerance in alfalfa. Our findings suggest that MsFtsH8 mitigates oxidative damage caused by drought by modulating the plant’s antioxidant system, thus improving drought tolerance in alfalfa. This study provides a molecular basis and candidate genes for enhancing drought resistance in alfalfa through genetic engineering.